Waiting to be heard [compact disc, unabridged] : a memoir - Knox, Amanda (HarperAudio, 2013)
She spent four years in a foreign prison for a crime she did not commit. Separated from her family, she was demonized by the international press and treated harshly by the Italian justice system, including disdainful police. She endured humiliation, injustice, and loneliness thousands of miles from her home. Now, with intelligence, grace, and candor, Amanda Knox, the young American exchange student, tells the full story of her harrowing ordeal in Italy.